Posted by
**jas20** on
.

can someone explain to me this please....

What is the difference between

ax^2+bx+c and ax^2+bx+c=0

One is an expression and the other is an equation. (An equation uses an equals sign.)

I hope this helps and is what you were asking.

well you got to equal it e.g:

3x-1=5

3x=5+1( for removing the "-1" you got to add 1 so you gotta do the same on the other side )

3x/3= 5/3( to remove the 3 from 3x as 3x= 3X x so you got to do the same both the side to keep it equal

1x=2

x=2

hope that the answer to your question!!